Can Gold Investments Provide a Good Hedge Against Inflation? An Empirical Analysis - Naser, Hanan (International Journal of Economics and Financial Issues, 2017)
It is widely accepted that inflation erodes purchasing power of retirement savings, redistributes wealth from lenders to borrowers, and threatens private investors’ long-term objectives. Thus, there is a high demand on diversifying investors portfolio for both individuals and institutions in order to hedge against inflation. This paper aims to examine the effectiveness of gold investments to hedge against consumer inflation risks in the United States (US). Using monthly data from April, 1986 to June, 2016, that covers more than 30 years, unit root testing approach robust for finite samples, the Johansen multivariate cointegration test procedure and vector error correction model (VECM) have been employed to examine the long-run relationship between gold return and consumer inflation in the US. The key finding suggests that gold investments in the US provide an effective hedge against inflation for investors who are willing to keep their investments for long-run. However, it does not provide any hedge if investors hold it for only short-term. Keywords: Hedge, Investments, Gold prices, Inflation, Cointegration JEL Classifications: C22; C52; G15; Q02